Sjögren’s Syndrome and Autoimmune Thyroid Disease: Two Sides of the Same Coin (2019)
The coexistence of Sjögren’s syndrome (SS) and autoimmune thyroid disease (AITD) has been documented. However, there is no consensus whether this coexistence should be considered as the same nosological condition or as polyautoimmunity. Thus, in this monocentric retrospective study, patients with SS alone (i.e., primary) were compared with patients with SS and AITD. In addition, a discussion of previous studies including those about genetic and environmental factors influencing the development of both conditions is presented. In our series, all patients with AITD had Hashimoto’s thyroiditis (HT). No significant differences in age, gender, age of disease onset, and disease duration were found between the two groups. Lymphadenopathy and urticaria were more frequently registered in patients with SS-HT than in patients with SS alone (p less than 0.05). Anti-Ro/SSA antibodies were more frequent in the primary SS group (p = 0.01). SS-HT patients were more likely to report a positive history of smoking (p = 0.03). The clinical expression of SS varies slightly when HT coexists. Although both entities share common physiopathological mechanisms as part of the autoimmune tautology, they are nosologically different and their coexistence should be interpreted as polyautoimmunity. Further studies based on polyautoimmunity would allow establishing a new taxonomy of autoimmune diseases. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.